Liquid anti-fire missiles. The method of extinguishing fires - Andrii Sokol; Halyna Sokol (Challenges and Issues of Modern Science)
Such types of fires as forest fires are becoming an increasingly acute problem around the world affecting life on our entire planet. In just the past few years, large fires have besieged a number of countries, including the United States, Canada, Australia, Turkey, and Brazil, and even such regions as Greenland and Northern Europe.